Appendix of Statistics: Conciliation Center of the Universidad de Los Andes Legal Aid Office (Centro de Conciliación del Consultorio Jurídico) (Spanish) - (:unkn) unknown (My University, 2016)
Statistical data on writs, requests and declarations.